1978
DOI: 10.1111/j.1365-2621.1978.tb07413.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SORBIC ACID AND SODIUM NITRITE ON Clostridium botulinum OUTGROWTH AND TOXIN PRODUCTION IN CANNED COMMINUTED PORK

Abstract: Experiments to determine the effect of sorbic acid alone and in combination with low nitrite and phosphate on botulinal toxin production in inoculated perishable, canned, cornminuted, cured pork were conducted. Forty-eight test lots of product were inoculated with approximately 100 spores per gram of five strains each of type A and B Clostridium botulinum. Twenty-five cans of each test lot were incubated at 27°C for up to 110 days. The time of swelling was recorded for each can and the first 10 swells per test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Our results support U.S. claims , Ivey & Robach, 1978) that potassium sorbate delayed the growth of CZ. botulinum in bacon containing Key as for Table 7. approximately 3.5% salt (on water) and 0 or low (40 pg/g) nitrite, and confirm the greater effectiveness of sorbate at 'low' pH (Sofos et af., 1980a).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results support U.S. claims , Ivey & Robach, 1978) that potassium sorbate delayed the growth of CZ. botulinum in bacon containing Key as for Table 7. approximately 3.5% salt (on water) and 0 or low (40 pg/g) nitrite, and confirm the greater effectiveness of sorbate at 'low' pH (Sofos et af., 1980a).…”
Section: Discussionsupporting
confidence: 91%
“…botutinurn in experimental bacons (Ivey et aZ., 1978) and canned comminuted pork (Ivey & Robach, 1978), to establish whether potassium sorbate also inhibited outgrowth of CZ. botulinum in this pork slurry system, which differs in several respects from the canned, comminuted pork above, and chicken-frankfurter emulsions of Sofos et al, (1979d).…”
Section: Discussionmentioning
confidence: 99%
“…Large increases in soluble orthophosphate content in sausages to which SAPP has been added might also be only indirectly related to bacterial inhibition in meat systems. Unlike other phosphates, SAPP induces a decrease in pH values of meat and meat products (Terre11 et al, 1982;Knipe, 1982;Hargett et al, 1980;Ivey and Robach, 1978), and its overall mode of action against bacteria may consequently be different from that of the alkaline phosphates. From this study and previous experiments with uncooked bratwurst, however, it was suggested that cooking SAPP-and STPP-containing bratwurst immediately after preparation was essential in retaining the antimicrobial properties of these phosphates, and that their use might provide a safety margin against clostridial growth in cooked meat products.…”
Section: Resultsmentioning
confidence: 99%
“…botulinum in pasteurized cured meats both in the U.S.A. (Christiansen et al, 1973(Christiansen et al, , 1974Tompkin, Christiansen & Shaparis, 1977, 1978aIvey & Robach, 1978;Ivey et ul., 1978;Sofos et al, 1979aSofos et al, ,b,c,d,e, 1980a and in the U.K. (Roberts et al, 1976(Roberts et al, , 1981a(Roberts et al, ,b,c, 1982.…”
Section: Introductionmentioning
confidence: 95%